2021
DOI: 10.3233/blc-200359
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health-Related Quality of Life Between Japanese and American Patients with Bladder Cancer as Measured by a Newly Developed Japanese Version of the Bladder Cancer Index

Abstract: INTRODUCTION: The aim of this study is to characterize health related quality of life (HRQOL) in Japanese patients after bladder cancer surgery and to perform cross-cultural comparison between Japanese and American patients. METHODS: Firstly, we cross-sectionally assessed HRQOL of 371 patients in Japan using the Bladder Cancer Index (BCI-Japanese). HRQOL of the four groups of patients (native bladder without intravesical therapy, native bladder with intravesical therapy, cystectomy with ileal conduit, and cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The mean scores for ICD and ONB were 87 (function: 84.6; bother 88.24) and 79.25 (function: 61.4; bother: 88.16), respectively, affirming the better urinary function in ICD participants with no major difference in urinary bother. Osawa et al reported similar results that the mean urinary function score was higher in ICD (89.2 ± 2.1) compared to ONB (52.5 ±2.8) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The mean scores for ICD and ONB were 87 (function: 84.6; bother 88.24) and 79.25 (function: 61.4; bother: 88.16), respectively, affirming the better urinary function in ICD participants with no major difference in urinary bother. Osawa et al reported similar results that the mean urinary function score was higher in ICD (89.2 ± 2.1) compared to ONB (52.5 ±2.8) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 64%
“…found no difference in sexual function between ICD and ONB. Of note, sexual bother did not differ significantly between ICD, ONB, native bladder without intravesical therapy, and native bladder with intravesical therapy ( 11 ). Japanese patients also had higher scores than our patients and the American study they used in their analyses regarding the sexual bother sub-domain ( 16 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation